Branch water uptake and redistribution in two conifers at the alpine treeline - Adriano Losso (Nature Portfolio, 2021)
Abstract During winter, conifers at the alpine treeline suffer dramatic losses of hydraulic conductivity, which are successfully recovered during late winter. Previous studies indicated branch water uptake to support hydraulic recovery. We analyzed water absorption and redistribution in Picea abies and Larix decidua growing at the treeline by in situ exposure of branches to δ2H-labelled water. Both species suffered high winter embolism rates (> 40–60% loss of conductivity) and recovered in late winter (< 20%). Isotopic analysis showed water to be absorbed over branches and redistributed within the crown during late winter. Labelled water was redistributed over 425 ± 5 cm within the axes system and shifted to the trunk, lower and higher branches (tree height 330 ± 40 cm). This demonstrated relevant branch water uptake and re-distribution in treeline conifers. The extent of water absorption and re-distribution was species-specific, with L. decidua showing higher rates. In natura, melting snow might be the prime source for absorbed and redistributed water, enabling embolism repair and restoration of water reservoirs prior to the vegetation period. Pronounced water uptake in the deciduous L. decidua indicated bark to participate in the process of water absorption.